Electrically pumped vertical external cavity surface emitting lasers suitable for passive modelocking - Barbarin, Yohan; Hoffmann, Martin; Pallmann, Wolfgang P.; Dahhan, Imad; Kreuter, Philipp; Miller, Michael; Baier, Johannes; Moench, Holger; Golling, Matthias; Suedmeyer, Thomas; Witzigmann, Bernd; Keller, Ursula (IEEE Journal of Selected Topics in Quantum Electronics, 2011)
Modelocked optically pumped vertical external cavity surface emitting lasers (VECSELs) have generated up to 6.4-W average power, which is higher than for any other semiconductor lasers. Electrical pumping of modelocked VECSELs is the next step toward a higher level of integration. With continuous wave (cw) electrically pumped (EP) VECSELs, an average output power of 900 mW has been demonstrated from the undisclosed proprietary novalux extended cavity surface emitting laser (NECSEL) design. In contrast, modelocked NECSELs have only been demonstrated at 40mW. Recently, we presented a numerical study of EP-VECSELs suitable for modelocked operation; here, we demonstrate the first realization of this design. Power scaling is achieved with a lateral mode size increase. The competing electrical and optical requirements are, on the electrical side, low ohmic resistance, and on the optical side, low optical losses and low dispersion. Additionally, the device needs to operate in a fundamental mode for stable modelocking. We have fabricated and characterized 60 EP-VECSELs with varying dimensions and compared their lasing performance with our numerical simulations. The tradeoff between good beam quality and output power is discussed with an outlook to the modelocking of these EP-VECSELs. Initial EP-VECSEL devices have generated > 100 mW of cw output power. © 2006 IEEE.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Modelocked lasers; optoelectronic devices; semiconductor lasers; vertical emitting lasers